Hubungan Mekanisme Koping Terhadap Kinerja Perawat Pelaksana Di Ruang Rawat Inap - Ardi - Septiyan; Erwin - -; Febriana - Sabrian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to determine the relation ship betwen of coping mechanism and the performance of associate nurses in ward of Eka Hospital Pekanbaru. The type of the research was correlation research with cross sectional design. Sample of this research were 63 nurses associate.The sampling technique used was total sampling. The data were analyzed by using Chi Square test . The result of this research showed that p-value = 0,102 > α (0,05 and conclude that there was no relation between coping mechanism and performance of associate nurse in ward of Eka Hospital Pekanbaru. It is recommended that management of hospital support and educate associate nurses to enhace performance and for associate nurses to optimize their self potential to increase performance. Keyword: Coping mechanism, performance, associate nurse